The Determinateness of the Utility Function - Lange, O. (Review of Economic Studies, 1934)
Journal Article The Determinateness of the Utility Function Get access O. Lange O. Lange Cracow and Cambridge, Mass. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 1, Issue 3, June 1934, Pages 218–225, https://doi.org/10.2307/2967485 Published: 01 June 1934